Can EU bonds serve as euro- denominated safe assets? - Tilman Bletzinger; William Greif; Bernd Schwaab (European Central Bank (ECB), 2022)
A safe asset is of high credit quality, retains its value in bad times, and is traded in liquid markets. We show that bonds issued by the European Union (EU) are widely considered to be of high credit quality, and that their yield spread over German Bunds remained contained during the 2020 Covid-19 pandemic recession. Recent issuances and taps under the EU's SURE and NGEU initiatives helped improve EU bonds' market liquidity from previously low levels, also reducing liquidity risk premia. Eurosystem purchases and holdings of EU bonds did not impair market liquidity. Currently, one obstacle to EU bonds achieving a genuine euro-denominated safe asset status, approaching that of Bunds, lies in the one-off, time-limited nature of the EU's Covid-19-related policy responses.
Keywords: E58; G12; H63; 330; European Central Bank; European Union; EU-issued bonds; NextGenerationEU (NGEU); market liquidity; Pandemic Emergency Purchase Programme (PEPP)